Seasonality of Holocene hydroclimate in the Eastern Mediterranean reconstructed using the oxygen isotope composition of carbonates and diatoms from Lake Nar, central Turkey - Dean, Jonathan R.; Jones, Matthew D.; Leng, Melanie J.; Metcalfe, Sarah E.; Sloane, Hilary J.; Eastwood, Warren J.; Roberts, C. Neil (SAGE, 2018)
A positive shift in the oxygen isotope composition (δ18O) of lake carbonates in the Eastern Mediterranean from the early to late Holocene is usually interpreted as a change to drier (reduced P/E) conditions. However, it has also been suggested that changes in the seasonality of precipitation could explain these trends. Here, Holocene records of δ18O from both carbonates and diatom silica, from Lake Nar in central Turkey, provide insights into palaeoseasonality. We show how Δδ18Olakewater (the difference between spring and summer reconstructed δ18Olakewater) was minimal in the early Holocene and for most of the last millennium, but was greater at other times. For example, between ~4,100-1,600 years BP we suggest that increased Δδ18Olakewater could have been the result of relatively more spring/summer evaporation, amplified by a decline in lake level. In terms of change in annual mean δ18O, isotope mass balance modelling shows that this can be influenced by changes in seasonal P/E as well as inter-annual P/E, but lake level falls inferred from other proxies confirm there was a mid Holocene transition to drier climatic conditions in central Turkey.